DNA Replication Controls - Eishi Noguchi (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The conditions for DNA replication are not ideal, owing to endogenous and exogenous replication stresses that lead to arrest of the replication fork. Arrested forks are among the most serious threats to genomic integrity because they can break or rearrange, leading to genomic instability, which is a hallmark of cancers and aging-related disorders. This title, "DNA Replication Controls", presents series of new reviews and original research articles, providing a comprehensive guide to theoretical advancements in the field of DNA replication research in both prokaryotic and eukaryotic systems. The topics include DNA polymerases and helicases; replication initiation; replication timing; replication-associated DNA repair; and replication of difficult-to-replicate genomic regions, including telomeres, centromeres and highly-transcribed regions. This title also provides recent advancements in studies of cellular processes that are coordinated with DNA replication and how defects in the DNA replication program result in genetic disorders, including cancer. Written by leading experts in DNA replication regulation, this book will be an important resource for a wide variety of audiences, including junior graduate students and established investigators who have interests in DNA replication and genome maintenance mechanisms.